Tunable luminescence of (Sr1−xCax)1.97MgSi2O7:0.03Eu2+ solid solution phosphors for cirtopic LEDs. (20th September 2019) - Wang, Wei; Jiang, Ziqiang; Wu, Ruixiang; Li, Chunjie; Yao, Ran; Wei, Xing; Guo, Tingting; Fan, Jibin; Ni, Lei; Duan, Li
Abstract: In order to realize the 490 nm single-peak emission for cirtopic light-emitting diodes (LEDs), a series of iso-structural (Sr1−x Cax )1.97 MgSi2 O7 :0.03Eu 2+ (x = 0, 0.2, 0.3, 0.4, 0.8, 1) phosphors with melilite structure have been prepared by traditional solid-state reaction. The x-ray Diffraction (XRD) patterns and regular lattice parameters confirm the formation of (Sr1−x Cax )2 MgSi2 O7 solid solution. Broad band excitation spectra were observed in the ultraviolet region of these phosphors. The photoluminescence spectra of (Sr1−x Cax )1.97 MgSi2 O7 :0.03Eu 2+ solid solution phosphors give continuously tunable emission from 466 [Sr2 MgSi2 O7: Eu 2+, (x = 0)] to 527 nm [Ca2 MgSi2 O7: Eu 2+, (x = 1)]. Phosphors with an illuminating centre at 486 and 490 nm were obtained when adjusting the x value to 0.3 and 0.4 respectively. By measuring the quantum efficiency (QE) and contrasting with the spectral sensitivity function of cirtopic, (Sr1−x Cax )1.97 MgSi2 O7 :0.03Eu 2+ (x = 0.3, 0.4) phosphors have potential value in cirtopic vision.